Muangnua arborea, a new semislug (Gastropoda, Stylommatophora, Helicarionidae, Durgellininae) from Loei Province, northeastern Thailand - Tumpeesuwan, Chanidaporn (Zookeys, 2019)
Abstract. Muangnua arborea Tumpeesuwan & Tumpeesuwan, sp. nov., is described, based on specimens deposited in the land snail collection of Mahasarakham University, Thailand. This species is the second described in the genus Muangnua, for which colour pictures of the living semislug in natural habitats, scanning electron microscope photos of the radula, and anatomy of the mature specimens were studied and presented for the first time for this genus. Keys to genera of Southeast Asian slug-like semislugs and species of Muangnua are provided.